1978
DOI: 10.1139/o78-100
|View full text |Cite
|
Sign up to set email alerts
|

Aminooxyacetic acid induced changes in γ-aminobutyrate metabolism at the subcellular level

Abstract: This paper is dedicated to the latt Dr. G . Malcolm Brown Wood, J. B., KuryIo, E. & Newstead, J. B. (1978) Aminooxyacetic acid induced changes in y-aminobutyrate nletabolism at the subcellular level. Can. J . Biochern. 56,667-672Aminooxyacetic acid (AOAA) (0.1 or 0.23 mmolikg) was administered to mice which were killed 1.5 and 6 h after treatment. Synaptosomal-and mitochondrial-enriched fractions were obtained by conventional ultracentrifugation procedures. The y-aminobutyric acid (GABA) content of the synapto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 3 publications
(3 reference statements)
2
17
0
Order By: Relevance
“…4): curves were obtained which resembled the uncorrected curves in Figure IA. This showed, in agreement with the findings of Wood et a1 [22] concerning treatment with aminooxyacetic acid, that a rapid initial increase of synaptosomal GABA is followed by an even greater augmentation of extrasynaptosomal GABA.…”
Section: Gaba Inhibitors and Distributionsupporting
confidence: 92%
See 1 more Smart Citation
“…4): curves were obtained which resembled the uncorrected curves in Figure IA. This showed, in agreement with the findings of Wood et a1 [22] concerning treatment with aminooxyacetic acid, that a rapid initial increase of synaptosomal GABA is followed by an even greater augmentation of extrasynaptosomal GABA.…”
Section: Gaba Inhibitors and Distributionsupporting
confidence: 92%
“…The following aspects have been considered in this work: 5) To what extent should synaptosomes be purified for the purpose of studying 6) Are drug-induced changes of cerebral GAHA associated with specific changes in 7) Are the observed changes of pool sizes consistent with the observed pharinacologic Independently of Wood and collaborators [22] we arrived at the same experimental procedure for the isolation of brains, and in agreement with them we found that high concentrations of amino acids in the homogenization medium d o not influence the synaptosonial concentrations, although under the usual experimental conditions GABA exchange was not insignificant and increased very much in the presence of elevated concentrations of exogenous GABA. In previous work [42] and again here we showed that synaptosomes purified by different centrifugation methods contain comparable GABA amounts if the determinations are based on synaptosomal protein and that the results are reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained from another group of rats (N = 10 rats per dose) 30 minutes after various doses of DPA are shown for purpose of comparison. strated marked effects of GABA-transaminase inhibition in nonneuronal cells and neural tissues that are not known to contain GABA terminals (15) as well as with subcellular fractionation studies (16). Since these compounds appear to affect nerve-terminal GABA only after other compartments of GABA have been elevated severalfold, it is understandable that relatively large increases in total GABA are required to elicit various GABA-related physiological effects with these drugs (17).…”
Section: I1 W S Broecker In Diffusion In Oceans Andmentioning
confidence: 99%
“…Administration to animals of inhibitors of yaminobutyrate-a-oxoglutarate aminotransferase (GABA; GABA-T) activity results in significant increases in the concentration of GABA both in nerve terminals (synaptosomes) and in other cellular structures in the brain, but the increase in GABA content of the latter structures is of a much greater magnitude (Wood et al, 1980~). Moreover, these drugs possess anticonvulsant properties that are related to the elevation of GABA levels in the synaptosomes.…”
mentioning
confidence: 99%
“…In contrast to the extensive research that has been carried out on the GABA-T inhibitors, in vivo studies with GABA uptake inhibitors have been more limited, due primarily to the lack of permeability of these compounds to the blood-brain barrier. This has necessitated the use of derivatives of the uptake inhibitors, which are metabolized in the brain tissue to the active compound (Frey et al, 1979), to the use of less potent inhibitors that do cross the blood-brain barrier (Wood and Hertz, 1980), or to the intracerebroventricular administration of the drugs (Horton et al, 1979). In spite of these restrictions, it is clear that inhibitors of GABA uptake do possess anticonvulsant properties (Frey et al, 1979;Horton et al, 1979;Wood, 1982), presumably due to their ability to increase the GABA concentration in the synaptic cleft by preventing reuptake of the amino acid into cellular structures.…”
mentioning
confidence: 99%